1999
DOI: 10.1021/ar990016y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivities of Cubane-Type Sulfido Clusters Containing Noble Metals

Abstract: Cubane-type sulfido clusters containing noble metals are newcomers compared with the corresponding clusters of the first transition series metals and molybdenum, which have been extensively studied in relation to metalloenzymes and industrial hydrodesulfurization catalysts. This Account reviews the recent progress in studies on the synthesis and reactivities of these noble metal cubane-type clusters. One of the goals in this new area lies in development of the unique catalysis of the noble metals embedded in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
100
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 250 publications
(101 citation statements)
references
References 45 publications
1
100
0
Order By: Relevance
“…[1] The bioinorganic significance of metal sulfide clusters is well known, and it has been put forward that the Mo 3 MЈS 4 (MЈ = Co, Ni) clusters in particular can constitute molecular models for the active sites of the industrial heterogeneous Co/MoS 2 or Ni/MoS 2 catalysts. [2] The Mo 3 PdS 4 4+ clusters catalyze nucleophilic addition to alkynes [3] and [Mo 3 NiS 4 (H 2 O) 10 ] 4+ has proved to be efficient in various heterogeneous catalytic processes. [4,5] Recently it was found that the heterometal in M 3 MЈS 4 4+ clusters (M = Mo, W; heterometal (MЈ) = Ni, Pd) stabilize very labile molecules of P(OH) 3 , RP(OH) 2 (R = H, Ph) and Ph 2 P(OH) by coordination at phosphorus [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1] The bioinorganic significance of metal sulfide clusters is well known, and it has been put forward that the Mo 3 MЈS 4 (MЈ = Co, Ni) clusters in particular can constitute molecular models for the active sites of the industrial heterogeneous Co/MoS 2 or Ni/MoS 2 catalysts. [2] The Mo 3 PdS 4 4+ clusters catalyze nucleophilic addition to alkynes [3] and [Mo 3 NiS 4 (H 2 O) 10 ] 4+ has proved to be efficient in various heterogeneous catalytic processes. [4,5] Recently it was found that the heterometal in M 3 MЈS 4 4+ clusters (M = Mo, W; heterometal (MЈ) = Ni, Pd) stabilize very labile molecules of P(OH) 3 , RP(OH) 2 (R = H, Ph) and Ph 2 P(OH) by coordination at phosphorus [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…[2] The Mo 3 PdS 4 4+ clusters catalyze nucleophilic addition to alkynes [3] and [Mo 3 NiS 4 (H 2 O) 10 ] 4+ has proved to be efficient in various heterogeneous catalytic processes. [4,5] Recently it was found that the heterometal in M 3 MЈS 4 4+ clusters (M = Mo, W; heterometal (MЈ) = Ni, Pd) stabilize very labile molecules of P(OH) 3 , RP(OH) 2 (R = H, Ph) and Ph 2 P(OH) by coordination at phosphorus [6][7][8] . Nonlinear optical properties of [M 3 (CuX)Q 4 (dmpe) 3 X 3 ]PF 6 (M = Mo, W; X = Cl, Br; Q = S, Se) were also studied.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Here we report a novel synthetic route based on the behavior of [L 2 Pt(µ-S) 2 PtL 2 ] compounds as metalloligands, which leads to multinuclear aggregates containing a {Pt 2 S 2 } n core. The synthetic strategy allows control of the nuclearity of the cluster and can be extended to other metals with square-planar coordination.…”
Section: Introductionmentioning
confidence: 99%